The political effects of the 1918 influenza pandemic in Weimar Germany - Stefan Bauernschuster; Matthias Blum; Erik Hornung; Christoph Koenig (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
How do health crises affect election results? We combine a panel of election results from 1893-1933 with spatial heterogeneity in excess mortality due to the 1918 Influenza to assess the pandemic's effect on voting behavior across German constituencies. Applying a dynamic differences-in-differences approach, we find that areas with higher influenza mortality saw a lasting shift towards left-wing parties. We argue that pandemic intensity increased the salience of public health policy, prompting voters to reward parties signaling competence in health issues. Alternative explanations such as pandemic-induced economic hardship, punishment of incumbents for inadequate policy responses, or polarization of the electorate towards more extremist parties are not supported by our findings.
Keywords: D72; I18; N34; H51; 330; Pandemics; Elections; Health; Voting behavior; Issue salience; Issue ownership; Weimar Republic